Fostering the emancipation of young people: Evidence from a Spanish rental subsidy - Ainhoa Aparicio Fenoll; Veruska Oppedisano (Institute for the Study of Labor (IZA), 2012)
In Southern Europe youngsters leave the parental home significantly later than in Northern Europe and United States. In this paper, we study the effect of a monthly cash subsidy on young adults' emancipation, family formation, and fertility. The subsidy, introduced in Spain in 2008, is conditional on young adults renting accommodation, and it amounts to almost 20 percent of the average youngsters' wage. Our identification strategy exploits the subsidy eligibility age threshold to assess the causal impact of the cash transfer. Difference-in-Differences and Regression Discontinuity estimates show that the policy increases emancipation rates by 0.9-2.3 percentage points, couple cohabitation by 1.2-2.4 percentage points, and the probability of having children by 4.8-8.1 percentage points for 22 year-olds compared to 21 year-olds. The effect is larger among young adults earning lower incomes and living in high rental price areas. This is consistent with the hypothesis that youngsters delay emancipation and family formation because they are budget constrained.
Keywords: J1; H2; I3; 330; rental subsidy; conditional cash transfer; youth emancipation; family formation; fertility; Jugendliche; Mietwohnung; Subvention; Familienpolitik; Wirkungsanalyse; Familiensoziologie; Spanien